The pains of immigrant imprisonment. Issue 11 (7th November 2016) - Longazel, Jamie; Berman, Jake; Fleury‐Steiner, Benjamin
Abstract: The immigrant detention system in the United States is civil, rather than criminal, and therefore nonpunitive. However, in practice, detained immigrants lacking many basic constitutional protections find themselves in facilities that are often indistinguishable from prisons and jails. In this paper, we explore the crisis of immigrant imprisonment at the affective level, focusing on the painful experiences of immigrant detainees, while also emphasizing its systemic and racialized nature. Specifically, we place a review of a growing body of research that draws connections between immigrant detention and mass imprisonment alongside the findings from numerous reports issued by human rights organizations on the conditions of confinement within immigrant detention facilities. Using a "pains of imprisonment" framework, we highlight four particularly prominent "pains": containment, exploitation, coercion, and legal violence . We suggest the infliction of such pain, especially when contextualized within a broader history of Latina/o oppression, demonstrates that immigration prisons are in fact punitive, "lawless spaces" where penal oppression is exercised. We conclude with a call for sociologists to become more attentive to this crisis, and to appreciate the similarities between immigration detention and other forms of racialized social control—namely, mass incarceration.